2014
DOI: 10.4081/aiua.2014.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Is there any effect of insulin resistance on male reproductive system?

Abstract: Despite of the documented strong inverse relationships between Diabetes Mellitus (DM) and male/female fertility, and also between IR and female infertility via ovarian functions as in polycystic ovary syndrome, to our knowledge, there is no report about any influence of IR on male fertility. DM and metabolic syndrome (MetS) have negative influence on fertility. Thus, IR may be accused of causing detrimental effect on male infertility due to hyperinsulinemic state and being one of the components for MetS. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the meantime, IR is directly associated with 1GF-1 levels (Friedrich et al, 2012;Sesti et al, 2005). However, an inverse correlation between IR and male reproductive functions could not be found (Verit et al, 2014). It has been demonstrated that parents and brothers (Sir-Petermann et al, 2002;Yildiz et al, 2003) and sons (Recabarren et al, 2008b) of PCOS women exhibit IR.…”
Section: Discussionmentioning
confidence: 94%
“…In the meantime, IR is directly associated with 1GF-1 levels (Friedrich et al, 2012;Sesti et al, 2005). However, an inverse correlation between IR and male reproductive functions could not be found (Verit et al, 2014). It has been demonstrated that parents and brothers (Sir-Petermann et al, 2002;Yildiz et al, 2003) and sons (Recabarren et al, 2008b) of PCOS women exhibit IR.…”
Section: Discussionmentioning
confidence: 94%
“…In a follow-up study, the authors reported that the low testosterone levels observed were not only associated with insulin sensitivity but also with markers of mitochondrial function (Pitteloud et al 2005b). Nonetheless, a recent study observed no relation between insulin resistance and male reproductive function (Verit et al 2014). These contradictory results might be related to the different patients' selection criteria and number.…”
Section: Testicular Levelmentioning
confidence: 96%
“…HOMA-IR is negatively correlated with serum T and progesterone (PR) (p<0.05). However, Verit and colleagues (38) observed that HOMA-IR shows no significant correlation with sperm count, motility, and morphology. Zag (zinc alpha glycoprotein) ( 39) is a new type of adipokines, which plays an important role in alleviating IR.…”
Section: Effect Of Insulin Resistance On Male Reproductionmentioning
confidence: 97%